2010
DOI: 10.1021/ja1016156
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Optoelectronic Properties of Membranes via Insertion of Amphiphilic Phenylenevinylene Oligoelectrolytes

Abstract: We report on the modification of membranes by incorporation of phenylenevinylene oligoelectrolytes with the goal of tailoring their optical and electronic properties and their applications. A water-soluble distyrylstilbene oligoelectrolyte (DSSN+), capped at each end with nitrogen bound, terminally charged pendant groups, was synthesized. The photophysical and solvatochromatic properties of DSSN+ and the shorter distyrylbenzene analogue DSBN+ were probed and found to be useful for characterizing insertion into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
253
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(268 citation statements)
references
References 92 publications
14
253
1
Order By: Relevance
“…As an intervening spacer, PPV molecular wires are an ideal choice because of their low attenuation values (26), synthetic tractability, and demonstrated ability to conduct current through lipid bilayers (31). Anilines are common PeT donors and the dialkyl groups should enhance uptake into the plasma membrane.…”
Section: Resultsmentioning
confidence: 99%
“…As an intervening spacer, PPV molecular wires are an ideal choice because of their low attenuation values (26), synthetic tractability, and demonstrated ability to conduct current through lipid bilayers (31). Anilines are common PeT donors and the dialkyl groups should enhance uptake into the plasma membrane.…”
Section: Resultsmentioning
confidence: 99%
“…DSSNϩ, 1,4-bis(4Љ-(N,N-bis(6ЉЉ-(N,N,N-trimethylammonium)hexyl)amino)-styryl)benzene tetraiodide (DSBNϩ), and 1,4-bis(4Љ-(N,N-bis(6ЉЉ-(N,N,N-trimethylammonium)hexyl)amino)-styryl)-2,3,5,6 tetrafluorobenzene tetraiodide (4F-DSBNϩ) were synthesized as reported previously (2,11). The MIMs used in this study were selected because their biotechnological potential had been demonstrated previously in bioelectrochemical systems and because interesting interactions with microbial cells have been documented (1,3,10).…”
Section: Methodsmentioning
confidence: 99%
“…Nisin is an amphiphilic broad-spectrum cationic antimicrobial peptide produced by Streptococcus lactis that is active against Gram-positive bacteria and which has been widely used in the food industry since the 1960s (2). Microbes that have acquired resistance to nisin have bulk changes in their membrane phospholipid head group composition and have been shown to contain less DPG than their wild-type counterparts.…”
Section: Aminoacylated Phospholipidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrode-driven reduction of carbon dioxide via acetogenic microorganisms, known as microbial electrosynthesis (13,14), is a strategy for conversion of CO 2 to organic commodities without a biomass intermediate. Biofilms of acetogenic microorganisms colonize surfaces of cathodes and directly convert CO 2 to organic products that are excreted from the cells.…”
mentioning
confidence: 99%